2022
DOI: 10.3389/fmed.2022.921452
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory therapies for COVID-19

Abstract: PurposeAs COVID-19 disease progresses, the host inflammatory response contributes to hypoxemia and severe and critical illness. In these latter stages of disease, patients may benefit from immunomodulatory therapies to control the aberrant host inflammatory response. In this review, we provide an overview of these therapies and provide summaries of the studies that led to issuance of FDA Emergency Use Authorization or recommendation by the Infectious Diseases Society of America (IDSA).Materials and methodsWe r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…and the amplification of the anti-inflammatory process. Furthermore, TLRs activation results in the release of type I interferon, which has a direct antiviral activity and activates the adaptive immune system [46][47][48]. Additionally, the NOD-like receptors (NLRs) sense the damage-associated molecular pattern (DAMP), released from dying and damaged cells, resulting in high levels of IL-1β, one of the main activators of IL-6 [46,49].…”
Section: Pathogenesismentioning
confidence: 99%
See 4 more Smart Citations
“…and the amplification of the anti-inflammatory process. Furthermore, TLRs activation results in the release of type I interferon, which has a direct antiviral activity and activates the adaptive immune system [46][47][48]. Additionally, the NOD-like receptors (NLRs) sense the damage-associated molecular pattern (DAMP), released from dying and damaged cells, resulting in high levels of IL-1β, one of the main activators of IL-6 [46,49].…”
Section: Pathogenesismentioning
confidence: 99%
“…Cytokine targeting and suppression could result in decreased proinflammatory signaling and improved clinical status [57]. Inhibition of IL-6, a key mediator of the inflammatory process in CS and a prognostic marker in COVID-19, with IL-6 receptor inhibitors including tocilizumab and sarilumab has shown its efficacy in the severe COVID-19 stages [1,48]. Earlier studies on tocilizumab had varying results and effectiveness was demonstrated in multiple studies [62][63][64], while others failed to show any clinical improvement in patients using tocilizumab compared to standard care [65].…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations